A prática como componente curricular em cursos de Licenciatura em Ciências Biológicas e em Química - Schmitz, Gabriela Luisa (2022)
Practice as a curricular component (PCC) is a component introduced in the workload of teacher training courses with the National Curriculum Guidelines (DCN) in 2002, aiming to promote the articulation between the practical and theoretical dimensions of teacher training. On the other hand, we recognize that the Biochemistry component involves complex and abstract concepts that can be difficult to learn both in undergraduate and basic education. Thus, we aimed to investigate the context of PCC in teacher training undergraduate courses in Biology and in Chemistry from three public brazilian institutions, as well as, (i) to describe how the practice as a curricular component appears in the official documents and in the undergraduate course projects in chemistry and biological sciences at UFSM, UFRGS, and IFFar Campus São Vicente do Sul; (ii) to scrutinize the conceptions of professors who teach subjects related to PCC; (iii) to analyze the potential of the Biochemistry area as a field for PCC in undergraduate courses in Chemistry and in Biological Sciences; and (iv) to propose an activity that can be developed in Biochemistry disciplines within the scope of the PCC. We used the Content Analysis methodology to analyze data obtained in pedagogical projects and with professors who teach subjects with a workload of PCC of the teacher training courses in Biological Sciences and in Chemistry at the Universidade Federal de Santa Maria, Universidade Federal do Rio Grande do Sul and do Instituto Federal Farroupilha. From the analysis of projects' data, we observed that the course documents are in line with the DCN in relation to the PCC, in terms of their workload, distribution, and objectives. When analyzing the teachers' answers, we found that most of them know the PCC and that they develop activities and evaluation methods that seek to meet the PCC's articulation objectives. However, some of the professors confuse the meaning of the word practice of the term PCC with laboratory practices and therefore, the evaluations they carry out are also in accordance with this conception. Also, teachers, in general, emphasize the contributions and relevance of PCC in teacher training as it contributes both to the realization of the supervised curricular internship and to future professional performance. We propose an activity that can be developed in the context of PCC that includes the concepts of biochemistry, specifically synthesis and protein structure of human insulin, which has the potential to be developed in basic education as well. Based on the results obtained in this research, we established the thesis that biochemistry may be an area with promising potential for PCC activities and approaches, contributing to the training of future Biology and Chemistry teachers.